2021
DOI: 10.1155/2021/5541181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Parameters on Hydration Heat Temperature and Thermal Stress of Mass Concrete

Abstract: To explore the influence of concrete thermal parameters on the hydration heat temperature and thermal stress of mass concrete, four feature positions of a dam foundation were chosen to analyze the changing process of temperature and stress by varying the thermal parameters, including the thermal conductivity, specific heat, surface heat diffusion coefficient, temperature rise coefficient, solar absorption coefficient, and thermal expansion coefficient. Some conclusions were obtained as follows. Increasing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In this field, the research team has carried out innovative researches in many aspects, such as rapid automatic dam modeling, substitution of the curtain of drainage holes by seeping layers for analysis on seepage field, model for simulating the real behaviors of transverse joints, efficient parallel algorithm for solving equations, method to determinate real parameters and criteria of concrete, etc., and formed the whole-process simulation & analysis method of concrete dam and SAPTIS simulation calculation program, which laid a foundation for studying the real working behaviors of concrete dams. It can display the spatiotemporal state and distribution of temperature and stress in various forms [16]. As shown in figure 2 for a typical expression of results.…”
Section: Whole-process and Whole-dam Simulation And Analysis Methodsmentioning
confidence: 99%
“…In this field, the research team has carried out innovative researches in many aspects, such as rapid automatic dam modeling, substitution of the curtain of drainage holes by seeping layers for analysis on seepage field, model for simulating the real behaviors of transverse joints, efficient parallel algorithm for solving equations, method to determinate real parameters and criteria of concrete, etc., and formed the whole-process simulation & analysis method of concrete dam and SAPTIS simulation calculation program, which laid a foundation for studying the real working behaviors of concrete dams. It can display the spatiotemporal state and distribution of temperature and stress in various forms [16]. As shown in figure 2 for a typical expression of results.…”
Section: Whole-process and Whole-dam Simulation And Analysis Methodsmentioning
confidence: 99%
“…Finally, these predictions were compared with the real-time monitoring results of the bridge foundation. Zhao et al [20] conducted numerical tests on hydration heat parameters and found that increasing the thermal conductivity of concrete and reducing the specific heat and temperature rise coefficient could reduce the maximum temperature of concrete. However, other thermal parameters showed no significant effect on the maximum temperature.…”
Section: Cmes 2024mentioning
confidence: 99%
“…To mitigate this, researchers have explored various materials. These include the use of the pipe cooling method (Zhang et al 2023), low heat cement (Jadhav 2021), microcapsules sustain release (MSR) as a sustained-release type hydration heat inhibitor (Jia et al 2021), reducing the amount of cement, selecting coarse aggregates with larger particle sizes and high thermal expansion coefficients (Zhao et al 2021), and using ground granulated blast furnace slag (GGBS) (Yalçınkaya et al 2021) to reduce the heat of hydration.…”
Section: Introductionmentioning
confidence: 99%
“…The heat of hydration is influenced by the type of mix and the size of the concrete. Some researchers have studied autogenous shrinkage for mass concrete (Kim et al 2009), and dams (Zhao et al 2021;Kim 2010), but not many have studied it for full-scale beam. There is a close relationship between heat of hydration and autogenous shrinkage at an early age, especially between HHV (hydration heating rate) and ASV (autogenous shrinkage rate).…”
Section: Introductionmentioning
confidence: 99%